2017
DOI: 10.1177/0894439317693332
|View full text |Cite
|
Sign up to set email alerts
|

Local Geographies of Digital Inequality

Abstract: Combining data from a sample survey, the 2013 Oxford Internet Survey, with the 2011 UK Census, we employ small area estimation to estimate Internet use in small geographies in Britain. This is the first attempt to estimate Internet use at any small-scale level. Doing so allows us to understand the local geographies of British Internet use, showing that the area with least use is in the North East, followed by central Wales. The highest Internet use is in London and southeastern England. The most interesting fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 39 publications
2
27
1
1
Order By: Relevance
“…This indicates that the digital divide between rural and urban areas cannot be solved by establishing infrastructure alone. This is consistent with Blank, Graham, and Calvino [15], who indicated that demographic factors have more of an impact on the digital divide than connectivity. While SNSs have become a fundamental tool for organizational or regional communication and promotion, more penetration of SNSs might escalate the second-level digital divide between disadvantaged rural areas and urban areas [9][10][11][12]44].…”
Section: Overall Adoption and Use Of Facebook In Disadvantaged Rural supporting
confidence: 89%
See 3 more Smart Citations
“…This indicates that the digital divide between rural and urban areas cannot be solved by establishing infrastructure alone. This is consistent with Blank, Graham, and Calvino [15], who indicated that demographic factors have more of an impact on the digital divide than connectivity. While SNSs have become a fundamental tool for organizational or regional communication and promotion, more penetration of SNSs might escalate the second-level digital divide between disadvantaged rural areas and urban areas [9][10][11][12]44].…”
Section: Overall Adoption and Use Of Facebook In Disadvantaged Rural supporting
confidence: 89%
“…Previous academic literature regarding ICT use for rural development has used case studies or analyzed national data. However, national data in terms of ICT use at the (joint) community level are not available in Japan as in other countries like the UK [15]. Thus, I needed to identify all rural (joint) communities that run (joint) community-based Facebook pages in Japan.…”
Section: Systematic Search For Facebook Pages With Titles Using Commumentioning
confidence: 99%
See 2 more Smart Citations
“…As a basic dimension, the respondent's demography is listed and presented. The demographic and inherent socio-economic background of people become notable factors when addressing ICT [52] and can be used to control the variables [53] to get more accurate results. In the questionnaire, these variables were asked: gender, age, education level, marital status, involvement as village organizer, and monthly spending (in IDR).…”
Section: Demographymentioning
confidence: 99%